Pengembangan suplemen bahan ajar digital kelas X materi penginderaan jauh menggunakan Heyzine Flipbook - Edisty Anindira Patranita; Yuswanti Ariani Wirahayu; Heni Masruroh; Hadi Soekamto (Universitas Negeri Malang, 2022)
During the last decade, digitalization has affected the structure of education in the world, this change requiring the conversion of conventional education in order to carry out practical and independent learning by students. The purpose of this research is to develop a validated digital teaching material supplement using remote sensing material. The Research and Development model is made following the ADDIE development steps, but is limited to the development stage. Teaching materials are created using Canva software and Heyzine Flipbook. The results of product validation, obtained an average of 91 percent and belonged to the very valid category. The results of the validation test are used as a reference for revision and refinement of teaching materials. Teaching materials were tested on teachers and students of class X IPS 1 SMAN 10 Malang, with a total of 36 students. In general, the test results were categorized as very good, with the test results on teachers amounting to 95 percent, and on students amounting to 92 percent. Based on the results of the trials that have been carried out, it can be seen that digital teaching material supplements are very good for use in learning activities. Selama dekade terakhir, digitalisasi mempengaruhi struktur pendidikan di dunia secara keseluruhan sehingga memerlukan konversi pendidikan konvensional agar terlaksana pembelajaran yang praktis dan mandiri oleh peserta didik. Penelitian ini bertujuan untuk mengembangkan suplemen bahan ajar digital pada materi penginderaan jauh menggunakan Heyzine Flipbook yang telah tervalidasi. Model penelitian pengembangan dibuat mengikuti langkah pengembangan ADDIE, namun dibatasi hingga tahap development. Bahan ajar dibuat menggunakan software Canva dan Heyzine Flipbook. Hasil validasi produk memperoleh rerata sebesar 91 persen dan tergolong pada kategori sangat valid. Hasil uji validasi digunakan sebagai bahan revisi serta penyempurnaan bahan ajar. Bahan ajar diujicobakan pada guru dan peserta didik kelas X IPS 1 SMAN 10 Malang, dengan jumlah siswa sebanyak 36 siswa. Secara umum, hasil uji coba mendapat kategori sangat baik, dengan skor uji coba pada guru sebesar 95, dan pada siswa sebesar 92 persen. Berdasarkan hasil uji coba, dapat diketahui bahwa suplemen bahan ajar digital sangat baik untuk digunakan pada pembelajaran.